Antioxidants in the Diet of Madinan Society in 622-632 A.D. - Nurul Mukminah binti Zainan Nazri (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
The purpose of this paper is to analyze antioxidant foods in the diet of Madinan society in 622-632 A.D. which is believed to be the time when the Prophet Muhammad dwelled in Madinah. Recently, Madinan society and other societies of the world were reported to have a depraved and unhealthy diet. This paper focuses on the Madinan diet to obtain a deeper understanding of a well-balanced diet as an exemplary dietary model for societies worldwide. This study is a qualitative study and the approach is content analysis. Data collected through the methods of content and document analysis are thematically analyzed using descriptive and analytical methods. Findings demonstrate that the variety of foods in the Madinan diet represents a complete and well-balanced diet. The implication of this study establishes that the foods in their diet contain beneficial antioxidant compounds. Thus, the dietary model of Madinan society can be recommended and served as one of the dietary models owing to its health benefits and its palatability.